Emergence of multidrug-resistant ST11 blaKPC-2 producing Klebsiella pneumoniae coharboring blaCTX-M and blaSHV in Pakistan - Jamal Gondal, Aamir; Saleem, Sidrah; Choudhry, Nakhshab; Jawad Ahmad, Fridoon; Bukhari, Hina; Yasmin, Nighat; Jahan, Shah (The Journal of Infection in Developing Countries, 2023)
Introduction: Carbapenemases are primarily responsible for the intensified spread of multidrug-resistant (MDR) K. pneumoniae by virtue of antibiotics overuse. Therefore, frequent investigation of high-risk clones especially from developing world is crucial to curtail global spread. Methodology: In this observational study, 107 K. pneumoniae were retrieved and confirmed genotypically from April 2018 to March 2020 from tertiary care hospitals in Lahore, Pakistan. Carbapenemases and extended-spectrum β-lactamases were verified by Polymerase Chain Reaction and Sanger sequencing. Multilocus sequence typing and plasmid replicon typing were used to assign clonal lineages and plasmid replicons. Results: Among the K. pneumoniae, 72.9% (78/107) strains were carbapenem resistant (CR) with 65.4% (51/78) exhibiting carbapenemase producing phenotype. Among CR K. pneumoniae 38.5% (30/78) strains exhibited the following carbapenemase genotypes: blaNDM-1 (26.7%, 8/30), blaOXA-48 (26.7%, 8/30), blaKPC-2 (20.0%, 6/30), blaVIM (10.0%, 3/30), blaNDM-1/blaOXA-48 (10.0%, 3/30), blaOXA-48/blaVIM (3.3%, 1/30) and blaOXA-48/blaIMP (3.3%, 1/30). Tigecycline and polymyxin-B retained susceptible profile. β-lactam drugs showed intermediate to high resistance. The occurrence of CR K. pneumoniae infections was significantly associated with wound (39.7%, p = 0.0007), pus (38.5%, p = 0.009), general surgery (34.6%, p = 0.002) and intensive-care unit (26.9%, p = 0.04). blaKPC-2 producing K. pneumoniae coharboring blaCTX-M/blaSHV (66.7%) and blaCTX-M (33.3%) exhibited sequence type (ST) 258 (n = 4) and ST11 (n = 2) sequence types with IncFII, IncN, IncFIIA, IncL/M and IncFIIK plasmids. Conclusions: This is the first report describing the emergence of MDR blaKPC-2 producing K. pneumoniae ST11 coharboring blaCTX-M and blaSHV in Pakistan.